Developing An Android App As A Maritime History Learning Media In Senior High School - Nuhiyah; Nana Supriatna; Leli Yulifar (EDUTEC : Journal of Education And Technology, 2022)
History learning is an efforts for maintaining maritime culture as part of the nation's identity. However, the maritime paradigm is still not an important issue for most Indonesians. Therefore, the learning of maritime history needs to be improved in order to strengthen national integration. One of the obstacles to learning maritime history is the lack of learning media about maritime history. This study aims to develop a maritime history learning media of the Sultanate of Banten based on an android application. The research method used is research and development (RND) with a 4-D development model (Define, Design, Develop and Dessiminate). The development of this media was carried out on the basis of the needs of history teachers and class X students in Banten for the learning media of maritime history of the Sultanate of Banten. The results of this study produced a learning media that has been created starting from the framework, its design, and the content of the material which is packaged into an Android Application product. The learning media for the Maritime History of the Sultanate of Banten based on the Android Application that was developed received a positive response from learning experts, linguists, media experts, teachers and students. The media trials for teachers and students show that the learning media developed is in accordance with the needs of students and teachers, providing student motivation in learning and making learning more enjoyable.